An efficient dye-sensitized NIR emissive lanthanide nanomaterial and its application in fluorescence-guided peritumoral lymph node dissection. Issue 26 (25th June 2018) - Liu, Qingyun; Zou, Xianmei; Shi, Yibing; Shen, Bin; Cao, Cong; Cheng, Shengming; Feng, Wei; Li, Fuyou
Abstract : Through combining Cy7 and NaYbF4 @NaYF4 :60%Nd together to form a dye-sensitized system, the near-infrared emission intensity of Yb was significantly enhanced. Abstract : The luminescence intensity of near-infrared (NIR) emitting lanthanide nanoparticles (LnNPs) is usually limited, owing to their small absorption cross section. Although dye sensitization has been proven to be an effective way to improve the luminescence intensity of LnNPs, the sensitization effect is fairly limited, owing to the simplicity of the sensitizers used and the complexity of the energy transfer process, typically involving three steps. In this study, a more efficient sensitizer (Cy7) was chosen to replace a commonly used one (ICG) and the energy transfer process was also optimized through using Yb 3+ ions as emitter ions and Nd 3+ ions as intermediate ions. With Cy7 as a sensitizer, the sensitization effect was assessed to be better than with ICG, owing to the higher quantum yield of Cy7. Meanwhile, the Cy7-sensitized NIR lanthanide nanomaterial was proven to be good for deep tissue penetration and low-power excitation bioimaging. Furthermore, the highly-enhanced NIR signal was successfully used in blood vessel imaging and fluorescence-guided peritumoral lymph node dissection in a mouse model.